Climatic roots of loss aversion - Oded Galor; Viacheslav Savitskiy (Brown University, Department of Economics, 2018)
This research explores the origins of loss aversion and the variation in its prevalence across regions, nations and ethnic group. It advances the hypothesis and establishes empirically that the evolution of loss aversion in the course of human history can be traced to the adaptation of individuals to the asymmetric effects of climatic shocks on reproductive success during the Malthusian epoch. Exploiting variations in the degree of loss aversion among second generation migrants in Europe and the US, as well as across precolonial ethnic groups, the research establishes that consistent with the predictions of the theory, individuals and ethnic groups that are originated in regions in which climatic conditions tended to be spatially correlated, and thus shocks were aggregate in nature, are characterized by greater intensity of loss aversion, while descendants of regions marked by climatic volatility have greater propensity towards loss-neutrality.
Keywords: D81; D91; Z10; 330; Loss Aversion; Cultural evolution; evolution of preferences; natural selection; Malthusian epoch